OP0131 Optimal dose of tocilizumab for the treatment of giant cell arteritis: efficacy, safety, and exposure-efficacy analysis from giacta. (15th June 2017) - Stone, JH; Tuckwell, K; Dimonaco, S; Klearman, M; Mallalieu, NL; Aringer, M; Blockmans, D; Brouwer, E; Cid, MC; Dasgupta, B; Rech, J; Salvarani, C; et al.
Abstract : Background: GiACTA, a randomized, double-blind, placebo-controlled trial, evaluated the efficacy and safety of tocilizumab (TCZ), an IL-6 receptor-α inhibitor, in patients with giant cell arteritis (GCA). 1, 2 Objectives: Secondary analyses to evaluate the differential efficacy and safety of TCZ between patients with new-onset and relapsing GCA and to evaluate the TCZ exposure-efficacy relationship at week 52 of the trial. Methods: Patients aged ≥50 years with active GCA were randomly assigned 1:1:2:1 to short-course prednisone (PBO+26), long-course prednisone (PBO+52) (26-week or 52-week prednisone taper + weekly subcutaneous [SC] placebo, respectively), weekly (TCZ-QW) or every-other-week (TCZ-Q2W) SC TCZ 162 mg + 26-week prednisone taper. Subgroup analysis was performed by disease-onset status (new-onset vs relapsing) to evaluate the proportions of patients in sustained remission at week 52 and time to flare. The impact of TCZ exposure, categorized into high, medium and low tertiles, on time to flare was evaluated across all patients in all treatment arms. Results: Randomization included 251 patients, 119 (47%) with new-onset and 132 (53%) with relapsing GCA, distributed evenly across groups. Higher proportions of patients achieved sustained remission in the TCZ vs placebo groups regardless of disease onset (new-onset, relapsing–TCZ-QW: 59.6%, 52.8%; TCZ-Q2W: 57.7%, 47.8%; PBO+26: 21.7%, 7.4%; PBO+52: 21.7%, 14.3%, respectively). Patients with relapsing disease at baseline were in relapse-free remission longer and thus had lower risk for flare (hazard ratio) when treated with TCZ-QW than TCZ-Q2W. Hazard ratio (99% CI) for flare vs PBO+26 was 0.23 (0.09–0.61) for TCZ-QW and 0.42 (0.14–1.28) for TCZ-Q2W; vs PBO+52 it was 0.36 (0.13–1.00) for TCZ-QW and 0.67 (0.21–2.10) for TCZ-Q2W. TCZ exposure-efficacy analysis showed that most patients in the low exposure tertile had been treated with TCZ-Q2W (80%) whereas those with medium and high exposure primarily received TCZ-QW (84% and 98%, respectively). Kaplan-Meier analysis demonstrated that patients with higher exposure benefited from a longer time to flare (Figure). Adverse events (AEs) were similar across groups. Serious AEs were reported in 15.0% TCZ-QW, 14.3% TCZ-Q2W, 22.0% PBO+26 and 25.5% PBO+52 patients; rates were similar between new-onset and relapsing patients. Conclusions: The compelling treatment effect of TCZ in GCA patients as measured by sustained remission to 52 weeks was consistent regardless of disease-onset status. Duration of relapse-free remission until flare was longer in patients with higher TCZ exposure, most notably in relapsing patients treated with TCZ-QW. References: Unizony SH et al. Int J Rheumatol. 2013;2013:912562. Stone JH et al. 2016 ACR/ARHP Annual Mtg; Washington, DC; A911. Disclosure of Interest: J. Stone Grant/research support from: Roche, Genentech, Xencor, Consultant for: Roche, Genentech, Xencor, K. Tuckwell Shareholder of: Roche, Employee of: Roche, S. Dimonaco Employee of: Roche Products Ltd., M. Klearman Employee of: Genentech, N. Mallalieu Shareholder of: Roche, Employee of: Roche, M. Aringer Speakers bureau: Roche, Chugai, D. Blockmans: None declared, E. Brouwer Consultant for: Roche, M. Cid Speakers bureau: Roche, Novartis, B. Dasgupta Speakers bureau: Roche, GlaxoSmithKline, J. Rech: None declared, C. Salvarani: None declared, G. Schett Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Lilly, Novartis, Roche, Sanofi, UCB, H. Schulze-Koops: None declared, R. Spiera Grant/research support from: Roche, Genentech, Consultant for: Roche, Genentech, S. Unizony: None declared, N. Collinson Employee of: Roche Products Ltd.